Atmospheric CO2 Consumption by Chemical Weathering in the Main Tributaries of the Yellow River: Tao He, Huang Shui, and Datong He, Originating From the Northeastern Qinghai-Tibet Plateau - Yongji, Zhuoma; Zhao, Liuqian; Li, Yunxiao; Zhang, Longjun (Frontiers in Earth Science, 2021)
The Tao He, Huang Shui, and Datong He originate from the northeastern margin of the Qinghai-Tibet Plateau (QTP) and flow into the Yellow River on the Loess Plateau (LP), all with a basin area exceeding 15,000 km2, and are the three largest tributaries of the Yellow River QTP sub-basin. Water samples were collected at the river outlets, the QTP section, the transition zone between the QTP and the LP, and the LP section of each river. These water samples were used to explore CO2 consumption by chemical weathering and its control mechanisms. Runoff and physical erosion are the main factors controlling chemical weathering in the three rivers. The increase of relief ratio in the transition zone between the QTP and the LP makes the chemical weathering particularly intense in this area. The total CO2 consumption rates by chemical weathering in the Tao He and Huang Shui transition zones are 1.4 times and 1.7 times greater than in their QTP sections, and 1.7 times and 2.3 times greater than in their LP sections, respectively. In contrast, due to the high relief ratio of 8‰ in the Datong He transition zone, the residence time of the water is extremely short, and unweathered fine-grained materials are delivered downstream to continue weathering. The influence of differential lithology distribution on chemical weathering includes that the Datong He QTP section with carbonate exposure presents the most intense carbonate weathering in that basin, and the Tao He transition zone has low silicate weathering resulting from the distribution of early Permian strata. In addition, groundwater recharge most likely influenced the silicate weathering of Huang Shui significantly. The total area of the three rivers accounts for 25% of the Yellow River QTP sub-basin, while their contribution to the total CO2 consumption flux by chemical weathering approximates 36%. The silicate weathering of the northern QTP rivers is lower than the global average and significantly lower than those of the southern QTP rivers. However, carbonate weathering of the QTP rivers exhibit no north-south regional differences.